2014
DOI: 10.1039/c4fo00013g
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceutical potential of Aerva lanata (L.) Juss. ex Schult ameliorates secondary complications in streptozotocin-induced diabetic rats

Abstract: Nutraceuticals provide health benefits beyond their basic nutrition by modulating a number of biochemical pathways. They are derived from natural products and have gained recognition worldwide as an adjuvant or therapy in the treatment of metabolic disorders such as diabetes. Although the regulation of blood glucose with drugs and insulin greatly reduces the incidence of secondary complications, the need for long-term treatment raises issues of tolerance and affordability. Therefore, the aim of the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…24 The rats in the normal control group were treated with the same volume of citrate buffer. 24 The rats in the normal control group were treated with the same volume of citrate buffer.…”
Section: Diabetes Induction and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…24 The rats in the normal control group were treated with the same volume of citrate buffer. 24 The rats in the normal control group were treated with the same volume of citrate buffer.…”
Section: Diabetes Induction and Experimental Designmentioning
confidence: 99%
“…After the rats were subjected to an overnight fasting, the rats were intraperitoneally injected with 60 mg per kg bw STZ (Sigma Chemicals, St. Louis, MO, USA) dissolved in 0.1 mol L −1 of citrate buffer ( pH 4.5). 24 The rats in the normal control group were treated with the same volume of citrate buffer. Three days after STZ was injected, the fasting blood glucose (FBG) of the rats was measured from the tail tip.…”
Section: Diabetes Induction and Experimental Designmentioning
confidence: 99%
“…Diabetes is a metabolic disorder associated with abnormalities in insulin production or secretion along with modifications in carbohydrate, fat and protein metabolism [96,97]. In accordance to, Riya et al, determined the presence of betulin, alpha amyrin and beta sitosterol in flower, leaf and roots of Aerva lanata [7,98].…”
Section: Anti-diabeticmentioning
confidence: 99%
“…In accordance to, Riya et al, determined the presence of betulin, alpha amyrin and beta sitosterol in flower, leaf and roots of Aerva lanata [7,98]. However, there are reports that betulin is useful in treatment of diabetes [99,100]. As 70% ethanolic extract (ALE) for 21 days in STZ-induced diabetic rat demonstrated that ALE was successful in refining postprandial hyperglycemia in sucrose-loaded normal and STZ diabetic rats, through its promising alpha glucosidase inhibitory potential [101,102].…”
mentioning
confidence: 96%
“…(AL; common name: polpala or mountain knotgrass) is a popular plant used in folk medicine. Due to its use in traditional medicine in the treatment of diabetes, arthritis, and urinary system diseases, the plant is of great interest to the pharmaceutical and nutraceutical industries [4]. A. lanata (L.) Juss.…”
Section: Introductionmentioning
confidence: 99%